EVALUATING ONLINE RESOURCES FOR ENGLISH LANGUAGE LEARNERS (ELL):A GUIDE TO FINDING QUALITY MATERIALS - Sevara Abdusharof qizi Mambetova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The aim of this article is to provide educators with a systematic approach for evaluating the quality of online resources available for English Language Learners (ELL). It seeks to equip educators with criteria—such as credibility, relevance, usability, and engagement—to critically assess and curate high-quality materials.